A Systematic Review of the Twelve Most Popular Bean Varieties, Highlighting Their Potential as Functional Foods Based on the Health Benefits Derived from Their Nutritional Profiles, Focused on Non-Communicable Diseases - Maria Dimopoulou; Patroklos Vareltzis; Olga Gortzi (Applied Sciences)
According to the US Department of Agriculture, more than 4000 types of beans are cultivated in the United States and worldwide; nevertheless, the demand for beans continues to rise. To some extent, diet can treat inflammation and consequently reduce the chances of developing comorbidities, such as diabetes. A diet based on alternative plant protein sources, such as beans, is a sustainable solution for overall health due to the overconsumption of meat that characterizes Western societies and is even more important for regions that suffer from malnutrition, such as Africa. Reviewing the nutritional profile of the different varieties of beans produced in various locations would help enhance their quality, strengthen the role of producer groups, and protecting Geographical Indications (GI), thereby increasing simplification, sustainability, and transparency towards consumers. PubMed-Medline, Web of Science, Scopus, and Cochrane Library databases were searched for relevant articles published by 30 March 2024. The results have given the green light to the reform of EFSA rules, strengthening the health claims of beans, protecting the GI for each variety, and also highlighting the public demands for functional foods based on the nutritional aspects of this product and its impact on disease management or prevention.